Effectiveness of Corruption Criminal Handling by the Polri Investor Parepare Resort Policy - Wahid, A. Ramlan; Mas, Marwan; Siku, H.Abd Salam (Postgraduate Bosowa University Publishing, 2018)
The study aims to investigation process has high effectiveness and factors influence the effectiveness of law enforcement of corruption by police investigators at Parepare Regional Police,and to find out and analyze the effectiveness of law enforcement on corruption by police investigators at Parepare Police Station; and 2) to know and analyze the factors that influence the effectiveness of law enforcement on corruption by police investigators at Parepare Regional Police. This research was a descriptive qualitative with a juridical-empirical approach. This approach examined the rules of positive law in other to get the answers to existing problems by linking with facts or phenomena about the effectiveness of law enforcement by investigators against corruption in Pare-Pare to fulfill the scientific prerequisites and factors that influence them. The population and sample were: 12 police officers, 8 police investigators, 5 prosecutors, 5 judges, 10 corruption perpetrators, and 10 community leaders. The results showed that 1. the handling of corruption cases by Pare-pare Police Corruption Unit period 2013 to 2017 had almost reached a high level of effectiveness. This was judged by the fulfillment ofthe target cases and each case was assessed in terms of completing the handling of corruption cases (P-21) so that in the meantime Parepare Police Corruption Unit does not experience delinquent police reports relating to corruption cases. 2. factors that influence the effectiveness of law enforcement by the investigators of Parepare Police Corruption Unit in handling corruption cases are both internal constraints and external constraints Internal constraints consist of the Legal Substance Factor, human resource factors and Legal Structure, the difficulty of finding evidence and, budget problems, while external constraints consist of Intervention (political) Factors and Community Legal Culture.